Influence of Heat Treatment on the Microstructure of a High Co-Ni Secondary Hardening Steel. (2015) - Gruber, M.; Ploberger, S.; Wiessner, M.; Marsoner, S.; Ebner, R.
Abstract: The aim of this study was to analyze the influence of combined heat and cryogenic treatment on the evolution of martensite and reverted austenite in a high Co-Ni steel. To this end the evolution of phase fractions and lattice constants after thermal treatments were characterized by using X-ray diffraction (XRD) investigations and dilatometer analyses. The arrangement of phases and the element distribution in martensite, austenite and carbides were analyzed by using energy filtered transmission electron microscopy (EFTEM).